A model for monitoring the evolution of the Black Sea ecosystem on the basis of remote sensing data assimilation. Issue 24 (17th December 2018) - Dorofeyev, V.; Sukhikh, L.
ABSTRACT: The study presents some results of the Black Sea ecosystem dynamics during about twenty years (1998–2016), based on numerical simulations with the assimilation of remote-sensing data. The 3D model of the lower trophic level marine ecosystem is a one-way, off-line coupled with circulation model. It describes processes in the layer from the sea surface to 200 m depth and includes 15 state variables. The ecosystem model assimilates the satellite measurements which are the maps of the surface chlorophyll concentration fields reconstructed based on the remote-sensing data from the Sea-viewing Wide Field-of-view Sensor (SeaWiFS, satellite OrbView) and Moderate Resolution Imaging Spectroradiometer (MODIS, satellites Aqua and Terra) using the regional optical model of the Black Sea. The assimilation technique is based on optimal interpolation and nudging procedure. The results of the simulation were validated using the Black Sea Oceanographic Database, which contains the direct measurements of chlorophyll, nitrates, and dissolved oxygen concentrations in seawater. Comparison of the simulation data with measurements showed that the simulated fields satisfactorily reproduce seasonal variability and vertical distribution. In addition to in situ measurements, the obtained surface chlorophyll distributions were also compared with the satellite data. The simulation results allowed analysing the inter-annual and seasonal variability of the main parameters of the Black Sea pelagic ecosystem. Evolution of the plankton biomass in the upper 50 m layer shows a negative linear trend, which is followed by reduction of the nitrates content in this layer.